Digital transitions in higher education during the pandemic: An exploratory study. - Aline Martins Costa (2022)
Educational process has changed in the last years, especially with the COVID-19 pandemic, resulting in a shift from face-to-face to emergency remote teaching. Considering this situation, the present study focuses on transitional education at a Portuguese Higher Education Institution, aiming to explore students' perspectives about their experiences during this period. This objective is unfolded in the following specific goals: to explore students' perspectives on the transitions between face-to-face and remote teaching; to understand the student's perspectives on the teaching-learning processes. Educational process has changed in the last years, especially with the COVID-19 pandemic, resulting in a shift from face-to-face to emergency remote teaching. Considering this situation, the present study focuses on transitional education at a Portuguese Higher Education Institution. This objective is unfolded in the following specific goals: to explore students' perspectives on the transitions between face-to-face and remote teaching; to understand the student's perspectives on the teaching-learning processes. This exploratory study follows a mixed approach, using an online questionnaire and a focus group. The results point to the need for adaptation by teachers and students to the different digital platforms that were used. The students emphasized the effort made by teachers to innovate strategies and create more interactive situations in class. On the other hand, students mentioned less positive aspects related to the difficulty accessing the internet, difficulty in time management, an increase of requests for individual and group work, as well as the maintenance of the old assessment modes, despite the new circumstances.